La dudosa legitimación de las resoluciones generales de la Inspección General de Justicia - Villarreal, Julio Francisco (2009)
In this essay, the validity of IGJ Resolutions N° 7/03 and N° 8/03\nis analized in the light of the delegation of functions made in favor of such\nbody by virtue of Act 22.315. The author states that said resolutions are\nunconstitutional, since they depart from the frame set by the legislative delegation,\nby means of which the IGJ is only authorised to control business\ntransaction of foreign corporations provided that they carry out habitual acts\nwithin the country. Therefore, the habituality requirement is being systematically set aside, distorting the legally established permission for said body\nto supervise corporations? activities. Besides, legislative, as well as case law\nevolution related to the subject throughout the century is also studied, laying\nspecial emphasis on the paradygmatic case entitled ?Inspección general de\nJusticia v. Frinet?